Flame-Retardant Ionic Conductive Elastomers with Multiple Hydrogen Bonds: Synthesis, Characterization, and Strain Sensing Applications - Sen Li; Hao Chen; Chen Zhao; Jinlin He; Lijing Zhang (Molecules)
Flammability is a significant challenge in polymer-based strain sensing applications. In addition, the existing intrinsic flame retardant is not elastic at room temperature, which may potentially damage the flexible equipment. This study presents a series of flame-retardant ionic conductive elastomers (ICEs) (denoted as PCAIPx) containing phosphorus from phytic acid (PA) and nitrogen from choline chloride (ChCl) with multiple hydrogen bonds synthesized using a simple and efficient one-pot UV-initiated radical copolymerization of a polymerizable deep eutectic solvent (PDES). The limiting oxygen index (LOI) value increased from 24.1% for the pure PCAI without PA to 38.3% for PCAIP7.5. The SEM analysis of the residual char shows that the formation of the dense and continuous char layer effectively worked as a shield, preventing further decomposition of the undecomposed polymer inside while hindering the transmission of heat and mass and isolating the oxygen required for combustion. The hydrogen bonds’ cross-linked structure and phosphorus-containing elastomer demonstrate a superior elasticity (elongation at break of up to 2109%), durability, and tear resistance and excellent adhesive properties. Application of PCAIPX in strain sensors showed that the elastomer has excellent cyclic stability and exhibited repeatable and stable resistance change signals in response to repetitive bending motions of the wrist, fingers, elbow, and knee. Consequently, this study provides a simple strategy for the development of a flame-retardant ICE which can effectively reduce fire hazards and potentially be applied in other fire-risk fields such as personal protection, firefighting, and sports equipment.